Probiotics for Trauma Patients: Should We Be Taking a Precautionary Approach?. Issue 1 (January 2017) - Vitko, Heather A.; Sekula, L. Kathleen; Schreiber, Martin A.
Abstract : The use of probiotics in the hospital setting is largely understudied and highly controversial. Probiotics are living organisms that, when taken internally, can produce an immunomodulating effect and improve the gastrointestinal (GI) mucosal barrier. Although used for centuries by healthy individuals for GI health, their use in the hospital setting is now gaining wide attention for the prevention of infectious complications such as antibiotic-associated diarrhea, Clostridium difficile infections, multiple-organ dysfunction syndrome, and ventilator-associated pneumonia. However, current understanding of the efficacy of probiotics in the acute care setting is confounded by the inconsistencies in the literature with regard to the strain of probiotic being studied, optimal dosage, and timing and duration of dosing, which make the formulation of clinical practice guidelines difficult. Although the safety of probiotics has been confirmed when used for the prevention and treatment of certain diseases, practitioners remain hesitant to administer them to their patients, citing the lack of high-quality studies clearly demonstrating efficacy and safety. Infection is a cause of late death in trauma patients, but only recently has research been conducted on the use of probiotics specifically for the prevention of hospital-acquired infections in trauma patients. In the face of such limited but promising research, is it reasonable to use probiotics for the prevention of infection in hospitalized trauma patients and improve outcomes? Use of the "precautionary principle" may be useful in this instance.